Forgiveness as a predictor of psychological well-being and aggression among young adult - Muhammad Yaseen; Zuhra Lal Bakhsh; Zalya Habeeb (Universitas Negeri Yogyakarta, 2025)
Forgiveness is widely recognized as a psychological process that enhances emotional well-being by reducing resentment and suppressing retaliatory impulses. Rooted in empathy and cognitive reappraisal, forgiveness is believed to mitigate negative evaluations of offenders. This study examines the relationship between forgiveness, psychological well-being, and aggression among young adults at the University of Balochistan, Quetta. A correlational research design was used, and a simple random sample of 200 students (100 males and 100 females) was selected. The Heartland Forgiveness Scale, Psychological Well-Being Scale, and Aggression Scale were administered. Pearson correlations revealed a significant positive relationship between forgiveness and psychological well-being, and a significant negative relationship between forgiveness and aggression. Reliability coefficients ranged between .80 and .86, indicating strong internal consistency. Independent sample t-tests also demonstrated notable gender differences across the study variables. The findings suggest that forgiveness contributes to enhanced psychological well-being and reduced aggressive tendencies among young adults. Promoting forgiveness-related skills may help foster emotional stability, life satisfaction, and healthier interpersonal behaviors within university populations.